Conflict: resolution and provention - BURTON, John (McMillan Publishing Company, 1993)
The first part of a set of four volumes which seeks to provide an historical and theoretical perspective for consideration of theory and practice in conflict resolution and provention. The authors puts forward an adequate theory of behaviour which they contend is needed to provide a basis for the analysis and resolution of conflict. The other volumes cover human needs theory and readings and practices in management and resolution in addition to a detailed description of the facilitated conflict resolution process.